2014
DOI: 10.1111/inr.12160
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of adolescents towards sexual health in three cities from Croatia and Bosnia and Herzegovina

Abstract: Providing care for adolescent populations should address specificities in local ethnical and socio-economical circumstances. There is a need for further studies to determine social, cultural and religious factors influencing the knowledge and attitudes towards sexual health in order to provide most effective interventions for specific adolescent populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…The more Human Behavior and Emerging Technologies positive attitudes toward sexting among Croatians compared to the Bosnian sample can be explained by the fact that Croatian youth come from a less traditional culture. Modern Croatian culture is characterized as liberal and permissive [69], which is also supported by the findings of Štulhofer et al [70], who found a clear trend towards more sexual permissiveness among young people from Croatia in the period from 1972 to 2005.…”
Section: Discussionsupporting
confidence: 75%
“…The more Human Behavior and Emerging Technologies positive attitudes toward sexting among Croatians compared to the Bosnian sample can be explained by the fact that Croatian youth come from a less traditional culture. Modern Croatian culture is characterized as liberal and permissive [69], which is also supported by the findings of Štulhofer et al [70], who found a clear trend towards more sexual permissiveness among young people from Croatia in the period from 1972 to 2005.…”
Section: Discussionsupporting
confidence: 75%
“…It was argued that knowledge of contraception, which students usually get and rely on from Peer groups/friends could be incomplete or false. 21 This exposes the students to risk of unintended pregnancy and contraction of STIs due to incorrect use of contraception as a result inadequate knowledge gotten from friends. Information between parents and their children with regards to contraception among these study participants was low.…”
Section: Discussionmentioning
confidence: 99%
“…Within nursing, shame is just beginning to be explored (Shaughnessy, in press). Much of the shame research that has been conducted in nursing is quantitative and focused on determining whether, and to what degree, shame is correlated with various health conditions (Kim & Im, 2015; Koç & Çinarli, 2015; Puharić, Borovac, & Petrov, 2015; Saint Arnault & O’Halloran, 2016; Wang et al, 2015). Qualitative studies have been conducted by nurse researchers who found shame to be a theme in the experience of a wide variety of health situations (Cleveland, Bonugli, & McGlothen, 2016; Gilmartin, 2013; Hawkins, 2017; Kantrowitz-Gordon, 2013; Lee, Li, Iamsirithaworn, & Khumtong, 2013; Navab, Negarandeh, Peyrovi, & Navab, 2013; Olsson & Berterö, 2015; Pollard, Fitzgerald, & Ford, 2015; Sparapani, Jacob, & Nascimento, 2015).…”
mentioning
confidence: 99%